Pengaruh Promosi terhadap Keputusan Mahasiswa Menabung di Bank Mini Syariah - Abdul Jamil (Al-Maqashid: Journal of Economics and Islamic Business, 2023)
The Small Sharia Bank Laboratory is a supporting and implementing facility for the Uin Sunan Ampel Surabaya program which is expected to be able to contribute to accelerating the development of sharia in Indonesia. Therefore, empowering the Mini Syariah Bank laboratory as a place to develop competencies both in the areas of intellectual, motor skills and skills in using Islamic banking media tools to increase the competency of Islamic finance and banking graduate students needs to be studied. This study aims to see the effect of promotion and knowledge on people's interest in making transactions at Mini Syariah Banks. The development of Islamic financial institutions in Indonesia has indeed experienced a significant increase, but this increase has not been accompanied by public knowledge about Islamic banks, especially in rural areas. So that in the end, many village people equate Islamic financial institutions with conventional financial institutions.